Developing vietnam electronic commerce in the period 2020 - 2025 - NGUYEN, TRAN HUNG (The journal of contemporary issues in business and government, 2021)
Vietnam e-commerce has a miraculous acceleration based on the advantages of a young population, the popularity of smart mobile devices along with the improvement of legal and payment platforms. and logistics. This fact has made Vietnam one of the fastest growing e- commerce markets in Southeast Asia. Not only that, Vietnam e-commerce is forecast to continue to grow rapidly in the period 2020 - 2025 with an annual growth rate of over 30%. However, the most important issue for e-commerce to continue to accelerate as expected and to develop stably is the need to objectively and accurately evaluate the results achieved as well as find out the shortcomings. , explaining the causes of the existing e-commerce market in Vietnam. The article has detailed the current situation of Vietnam e-commerce market, as well as based on statistics and market outlook forecasts of reputable e-commerce research organizations in Vietnam as well as in the world to propose solutions in order to develop e-commerce in Vietnam to a new high level.